pp60v-src tyrosine kinase is expressed and active in sarcoma-free avian embryos microinjected with Rous sarcoma virus. - Howlett, A R (1988)
Early embryonic avian tissue is resistant to transformation by Rous sarcoma virus. To determine the nature of this resistance, we examined the expression and properties of the Rous sarcoma virus transforming protein pp60v-src, in infected embryonic chicken limbs in ovo. Lysates from Rous sarcoma virus-infected limbs contained the viral structural protein p19gag, as detected by immunoblot analysis, and showed pp60v-src kinase activity in vitro. Immunoblot analysis of lysates with anti-phosphotyrosine antibodies revealed a number of phosphotyrosine-containing proteins present in lysates of Rous sarcoma virus-infected embryos but not in lysates of control, uninfected embryos. Anti-phosphotyrosine immunoreactivity was observed in frozen sections in the same cell types that expressed pp60v-src and p19gag. These studies demonstrate that pp60v-src is co-expressed with viral structural determinants in infected embryonic avian tissue. Furthermore, pp60v-src is active in ovo as a tyrosine-specific phosphotransferase, despite the apparent lack of sarcoma induction. The localization pattern of the major src gene substrate p36 (calpactin I) was compared with that of p19gag by double-label immunofluorescence and found to be generally nonoverlapping. These observations are consistent with the concept that the induction of tumors in ovo requires complementation between viral determinants and host factors. These host factors, which may be critical substrates of pp60v-src, are subject to developmental regulation in the avian embryo.